BASIS FOR SELECTION OF RIVERS FOR MONITORING ON THE STOCKS OF CHUM AND PINK SALMON IN THE AMUR RIVER - S. F. Zolotukhin (Известия ТИНРО, 2019)
The monitoring of chum and pink salmon escapement to spawning grounds in the Amur River basin was stopped in 2009. To start it again, a proved choice of the rivers is necessary for adequate controlling of these species number, by the spawning habitats of their population groups within the basin. For this purpose, results of the monitoring in 1949–2000 and the data on human settlements in the medieval times are analyzed. The lower reaches of the Amur were anciently inhabited by the paleoasiatic Nivkh people and the upper reaches where the fall chum spawned in spring waters were inhabited by the people of Pokrovskaya archeological culture — their burial grounds coincided with the spawning area of fall chum salmon. To reach these spawning grounds, fall chum salmon migrated up to the distance of 3427 km from the Amur mouth, but since the 20th century they occur rarely in the upper reaches of the Amur, in particular within Chinese territory where they are not observed in more than 50 years; recently they spawn in spring waters at the distance 500–1200 km from the Amur mouth, mainly in its right tributaries. The reproduction centers of other two populations of chum salmon, as the summer chum and fall chum breeding in hyporheic waters, are located in the Amgun River basin (the lower left tributary of the Amur). The fourth population is the lake chum salmon breeding in spring waters of Lake Chlya located on the left bank in the lower reaches of the Amur River. Centers of reproduction for both pink salmon populations, differentiated by even and odd years of spawning, are located in the Amgun River. Several test rivers are selected within all mentioned centers of reproduction, they are: Kerbi, Duki, Im, Somnya, Aksha, Khilka, Beshenaya, Gur, Anui, Khor, Kur, and Bira. This list is similar to the list of the rivers where chum and pink salmons were monitored in the 20th century